Composite sheet and method for manufacturing a composite sheet

JP2026166642APending Publication Date: 2026-10-14ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059709
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、高い導電性及び高い強度を両立した複合シートを提供できる。 また、本発明によれば、高い導電性及び高い強度を両立した複合シートの製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166642000001
    Figure 2026166642000001
Patent Text Reader

Abstract

To provide a composite sheet that achieves both high conductivity and high strength. [Solution] The present invention relates to a composite sheet comprising carbon nanotubes and reduced graphene oxide, wherein, on at least one surface of the composite sheet, the ratio of the area B of the area where reduced graphene oxide is exposed to the area A of the area where the carbon nanotubes are exposed is 0.1 or more and 50.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a composite sheet and a method for manufacturing a composite sheet. [Background technology]

[0002] In recent years, attempts have been made to use graphene and carbon nanotubes as electrode materials in capacitors with the aim of improving the performance of capacitor electrodes.

[0003] For example, Patent Document 1 describes a film density of 1.1 g / cm³ with the aim of reducing the curve ratio and electrical resistance. 3 More than 1.3g / cm 3 The following has been proposed: a mixed film of reduced graphene oxide (rGO) and carbon nanotubes (CNTs) (rGO / CNT mixed film), in which the ratio of oxygen atoms to carbon atoms (O / C), determined by X-ray photoelectron spectroscopy, is less than 0.3; and a capacitor using this rGO / CNT mixed film as an electrode. Furthermore, Patent Document 1 discloses a reduction treatment of a mixture of an aqueous solution of graphene oxide (rGO) and an aqueous solution of carbon nanotubes (CNTs) using hydrazine. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2022-80406 [Overview of the project] [Problems that the invention aims to solve]

[0005] In this regard, there was room for further improvement in achieving both high conductivity and high strength in the mixed film (composite sheet) using graphene and carbon nanotubes.

[0006] Therefore, the present invention aims to provide a composite sheet that achieves both high conductivity and high strength. Furthermore, the present invention aims to provide a method for manufacturing a composite sheet that achieves both high conductivity and high strength. [Means for solving the problem]

[0007] The inventors diligently conducted research with the aim of solving the above problems. The inventors have newly discovered that the above problems can be solved if the composite sheet contains carbon nanotubes (hereinafter sometimes referred to as "CNT") and reduced graphene oxide (hereinafter sometimes referred to as "rGO"), and the ratio of the area B of the area where reduced graphene oxide is exposed to the area A of the area where carbon nanotubes is exposed (area B / area A) on at least one surface of the composite sheet is within a predetermined numerical range, and have completed the present invention.

[0008] In other words, the present invention aims to advantageously solve the above problems, and [1] the present invention is a composite sheet comprising carbon nanotubes and reduced graphene oxide, wherein on at least one surface of the composite sheet, the ratio of the area B of the area where the reduced graphene oxide is exposed to the area A of the area where the carbon nanotubes are exposed is 0.1 or more and 50.0 or less. The composite sheets described above achieve both high conductivity and high strength. In this specification, "graphene" means a structure in which carbon atoms are arranged in a honeycomb pattern in one or more layers (for example, one to five layers). In this specification, "graphene oxide" means graphene having an oxygen-containing functional group bonded to the carbon atoms of graphene. Examples of oxygen-containing functional groups include epoxy groups (-COC-), hydroxyl groups (-OH), carbonyl groups (-CO-), and carboxyl groups (-COOH). In this specification, "reduced graphene oxide" means a partially reduced form of graphene oxide. In this specification, the area A of the region where carbon nanotubes are exposed (hereinafter sometimes simply referred to as "Area A") and the area B of the region where reduced graphene oxide is exposed (hereinafter sometimes simply referred to as "Area B") can be calculated according to the method described in the examples of this specification.

[0009] [2] In the composite sheet described in [1] above, the membrane density is 0.10 g / cm³. 3 More than 1.40g / cm 3 The following is preferable: If the film density is above the lower limit mentioned above, the conductivity and strength of the composite sheet can be effectively improved. On the other hand, if the film density is below the above upper limit, electrodes and other components using the composite sheet can be effectively made lighter. Furthermore, the flexibility of the composite sheet can be effectively maintained. In this specification, the "membrane density" of a composite sheet can be measured according to the method described in the examples of this specification.

[0010] [3] In the composite sheet described in [1] or [2] above, the film thickness is preferably 5 μm or more and 100 μm or less. If the film thickness is above the lower limit mentioned above, the strength of the composite sheet can be effectively improved. On the other hand, if the film thickness is below the above upper limit, the flexibility of the composite sheet can be effectively improved. In this specification, the "film thickness" of a composite sheet can be measured according to the method described in the examples of this specification.

[0011] [4] In any of the composite sheets described in [1] to [3] above, the mass ratio of reduced graphene oxide to carbon nanotubes (reduced graphene oxide / carbon nanotubes) is preferably 0.02 or more and 0.50 or less. If the mass ratio of reduced graphene oxide to carbon nanotubes is above the lower limit mentioned above, the strength of the composite sheet can be effectively improved. On the other hand, if the mass ratio of reduced graphene oxide to carbon nanotubes is below the above upper limit, the conductivity of the composite sheet can be effectively improved.

[0012] Further, the present invention aims to advantageously solve the above problems, and [5] the present invention relates to a composite sheet comprising carbon nanotubes and reduced graphene oxide, which is obtained by heating and reducing a pre-composite sheet formed by removing a solvent from a dispersion containing the carbon nanotubes, graphene oxide and the solvent. The composite sheet as described above achieves both high electrical conductivity and high strength.

[0013] Further, the present invention aims to advantageously solve the above problems, and [6] the present invention relates to a method for producing a composite sheet containing carbon nanotubes and reduced graphene oxide, the method comprising: a dispersion preparation step of preparing a dispersion containing the carbon nanotubes, graphene oxide and a solvent; a pre-composite sheet forming step of removing the solvent while the dispersion is placed on a base material to form a pre-composite sheet; and a thermal reduction step of heating the pre-composite sheet to reduce the graphene oxide in the pre-composite sheet. With the method for producing a composite sheet as described above, a composite sheet that achieves both high electrical conductivity and high strength can be obtained.

[0014] [7] In the method for producing a composite sheet according to the above [6], the reduction is preferably performed at a temperature of 200°C or higher under a vacuum atmosphere or an inert gas atmosphere. If the reduction is carried out at a temperature of 200°C or higher under a vacuum atmosphere or an inert gas atmosphere, graphene oxide can be reduced more efficiently. [Advantageous Effects of Invention]

[0015] According to the present invention, a composite sheet that achieves both high electrical conductivity and high strength can be provided. Further, according to the present invention, a method for producing a composite sheet that achieves both high electrical conductivity and high strength can be provided. [Mode for Carrying Out the Invention]

[0016] Each component disclosed herein, as well as preferred embodiments, numerical ranges, and thresholds defining such numerical ranges, can be independently combined with each other in any manner.

[0017] Embodiments of the present invention will be described in detail below. Herein, the composite sheet of the present invention is not particularly limited, but can be used, for example, as an electrode for a capacitor or the like. The composite sheet of the present invention can be obtained by the method for manufacturing the composite sheet of the present invention, as described later.

[0018] (Composite sheet) The composite sheet of the present invention comprises carbon nanotubes and reduced graphene oxide, and the composite sheet of the present invention has a ratio (area B / area A) of 0.1 or more and 50.0 or less of the area B of the area B of the area B of the area B of the area B of the area B of the area A of the area B of the area B of the area B of the area B of the area C of the area C of the area C of the area C of the area A The composite sheet described above achieves both high conductivity and high strength. This is presumed to be because, in composite sheets where area B / area A is within the above range, the CNTs and rGO are in appropriate contact within the composite sheet, thereby effectively reducing the resistance of the composite sheet, and the CNTs intertwine well with each other within the composite sheet, effectively suppressing fracture of the composite sheet. Furthermore, the composite sheet of the present invention is preferably a single-layer sheet in which CNTs and rGO are dispersed.

[0019] In the composite sheet, the mass ratio of rGO to CNT (rGO / CNT) is preferably 0.02 or higher, more preferably 0.04 or higher, preferably 0.50 or lower, more preferably 0.25 or lower, even more preferably 0.15 or lower, and even more preferably 0.10 or lower. If the mass ratio of rGO to CNT is above the lower limit mentioned above, the strength of the composite sheet can be effectively improved. On the other hand, if the mass ratio of rGO to CNTs is below the above upper limit, the conductivity of the composite sheet can be effectively improved.

[0020] The total proportion of CNTs and rGO in the composite sheet is preferably 50% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and most preferably 99% by mass or more.

[0021] The composite sheet may contain components other than the CNTs and rGO described above (hereinafter sometimes referred to as "other components"), but the content of the other components in the composite sheet is preferably 30% by mass or less, more preferably 20% by mass or more, even more preferably 10% by mass or less, and even more preferably 5% by mass or less. Other ingredients include, for example, graphene oxide (hereinafter sometimes referred to as "GO").

[0022] <Properties of composite sheets> The ratio of the area B of the region where rGO is exposed to the area A of the region where CNTs are exposed in the composite sheet (area B / area A) must be 0.1 or more, preferably 0.2 or more, more preferably 0.3 or more, must be 50.0 or less, preferably 40.0 or less, more preferably 30.0 or less, even more preferably 10.0 or less, even more preferably 1.0 or less, and even more preferably 0.5 or less. If the ratio of area B to area A is within the above range, the conductivity and strength of the composite sheet can be effectively improved.

[0023] The membrane density of the composite sheet is 0.10 g / cm³. 3 Preferably, it should be 0.30 g / cm³ or more. 3 It is more preferable that the value be greater than or equal to 0.60 g / cm³. 3 It is even more preferable that the amount be greater than or equal to 1.40 g / cm³. 3is preferably not more than, 1.00 g / cm 3 is more preferably not more than, 0.80 g / cm 3 is even more preferably not more than, 0.70 g / cm 3 is particularly preferably not more than. When the film density is at or above the aforementioned lower limit, the electrical conductivity and strength of the composite sheet can be effectively improved. On the other hand, when the film density is at or below the aforementioned upper limit, electrodes and the like using the composite sheet can be effectively reduced in weight. In addition, the flexibility of the composite sheet can be effectively maintained.

[0024] The film thickness of the composite sheet is preferably 5 μm or more, more preferably 7 μm or more, even more preferably 10 μm or more, preferably 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less, and particularly preferably 15 μm or less. When the film thickness is at or above the aforementioned lower limit, the strength of the composite sheet can be effectively improved. On the other hand, when the film thickness is at or below the aforementioned upper limit, the bendability of the composite sheet can be effectively improved.

[0025] The electrical conductivity of the composite sheet is preferably 60.0 S / cm or more, more preferably 70.0 S / cm or more, even more preferably 80.0 S / cm or more. The electrical conductivity of the composite sheet is, for example, 1000.0 S / cm or less, and may be 200.0 S / cm or less. In the present specification, the electrical conductivity of the composite sheet can be measured according to the method described in the Examples of the present specification.

[0026] The breaking strength of the composite sheet is preferably 10.0 MPa or more, more preferably 20.0 MPa or more. The breaking strength of the composite sheet is, for example, 500.0 MPa or less, and may be 200.0 MPa or less. In the present specification, the breaking strength of the composite sheet can be measured according to the method described in the Examples of the present specification.

[0027] Furthermore, the properties of the composite sheet described above can be adjusted, for example, by the manufacturing conditions of the composite sheet, the amount of raw materials used in the composite sheet, etc.

[0028] <Carbon nanotubes> Here, carbon nanotubes (CNTs) are nanocarbon materials having a structure in which graphene sheets are wound into a cylindrical shape, and are broadly classified into single-walled CNTs and multi-walled CNTs based on the number of components in their peripheral walls. The CNTs included in the composite sheet are not particularly limited, and both single-walled CNTs and multi-walled CNTs can be used, but it is preferable to use single-walled CNTs because it can increase the contact area with rGO, and as a result, the strength and conductivity of the composite sheet can be more effectively enhanced. In this specification, "single-walled carbon nanotubes (CNTs)" refers to carbon nanotubes (CNTs) in which the number of carbon atoms constituting the CNT tube walls is 1 or more but less than 2, and "multi-walled carbon nanotubes (CNTs)" refers to carbon nanotubes in which the number of carbon atoms constituting the CNT tube walls is 2 or more. Here, the number of tube walls refers to the average number of layers of the CNT, which can be determined by measuring the number of layers of 100 or more CNTs using a transmission electron microscope (TEM) on the dried aqueous dispersion of CNTs.

[0029] The average diameter (Av) of the CNTs is preferably 0.5 nm or more, more preferably 1 nm or more, preferably 15 nm or less, and more preferably 10 nm or less.

[0030] For carbon nanotubes (CNTs), it is preferable that the mean diameter (Av) and the standard deviation of the diameter (3σ) satisfy the relationship: 0.60 > "3σ / Av" > 0.20.

[0031] In this specification, "average diameter (Av)" and "diameter distribution (3σ)" are the average value and standard deviation (σ) obtained by multiplying by 3, respectively, of the diameters (outer diameters) of 100 randomly selected carbon nanotubes (CNTs) measured using a transmission electron microscope. Note that the standard deviation used in this specification is the sample standard deviation.

[0032] The BET specific surface area of ​​CNT is 600m². 2 It is preferable that it be 1 / g or more, and 800m 2 It is more preferable that it be 1000m or more per gram. 2 It is even more preferable that the amount be 1 / g or more. In this specification, the BET specific surface area of ​​CNTs is the nitrogen adsorption specific surface area measured using the BET method.

[0033] For CNTs, the ratio of the G-band peak intensity to the D-band peak intensity in the Raman spectrum (G / D ratio) is preferably 0.5 or higher, and preferably 5.0 or lower.

[0034] Here, the CNTs having the above-described properties are not particularly limited, and for example, CNTs produced in accordance with a method (super-growth method; see International Publication No. 2006 / 011655) in which raw material compounds and a carrier gas are supplied to a substrate having a catalyst layer for CNT production on its surface, and when CNTs are synthesized by chemical vapor deposition (CVD), a small amount of oxidizing agent (catalyst activator) is present in the system to dramatically improve the catalytic activity of the catalyst layer. In the following, carbon nanotubes obtained by the supergrowth method may be referred to as "SGCNT".

[0035] The CNT content in the composite sheet is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, preferably 99% by mass or less, and more preferably 97% by mass or less. If the carbon nanotube content in the composite sheet is within the above range, the conductivity of the composite sheet can be effectively improved.

[0036] <Reduced Graphene Oxide> As described above, reduced graphene oxide (rGO) is a partially reduced form of graphene oxide (GO). That is, rGO may have oxygen-containing functional groups such as epoxy groups (-COC-), hydroxyl groups (-OH), carbonyl groups (-CO-), and carboxyl groups (-COOH).

[0037] Here, the GO that can be used to form rGO can be prepared using various synthesis methods, such as the Hummers method, the Modified Hummers method, or the oxidation of graphites.

[0038] The rGO content in the composite sheet is preferably 1% by mass or more, more preferably 3% by mass or more, preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 20% by mass or less, and even more preferably 10% by mass or less. If the rGO content in the composite sheet is within the above range, the conductivity of the composite sheet can be effectively improved.

[0039] (Composite sheet according to another embodiment) Another embodiment of the present invention provides a composite sheet comprising carbon nanotubes and reduced graphene oxide. The composite sheet is obtained by heating and reducing a pre-composite sheet formed by removing the solvent from a dispersion containing carbon nanotubes, graphene oxide, and a solvent. The composite sheet described above achieves both high conductivity and high strength. This is presumed to be because, in such a composite sheet, the CNTs and rGO are in appropriate contact, thereby effectively reducing the resistance of the composite sheet, and the CNTs intertwine well with each other within the composite sheet, effectively suppressing fracture of the composite sheet. Furthermore, the properties of the composite sheet described above, the components that may be included in the composite sheet (CNT, rGO, other components, etc.), etc., can also be applied to the composite sheet according to another embodiment of the present invention.

[0040] (Method of manufacturing composite sheets) The present invention relates to a method for producing a composite sheet (hereinafter sometimes simply referred to as the "production method"), which comprises carbon nanotubes and reduced graphene oxide. The production method of the present invention comprises a dispersion preparation step of preparing a dispersion containing carbon nanotubes, graphene oxide, and a solvent; a pre-composite sheet formation step of removing the solvent while the dispersion is placed on a substrate to form a pre-composite sheet; and a heating and reduction step of heating the pre-composite sheet to reduce the graphene oxide in the pre-composite sheet. With the manufacturing method described above, a composite sheet that achieves both high conductivity and high strength can be obtained. Furthermore, with the manufacturing method described above, the composite sheet of the present invention described above can be obtained.

[0041] The manufacturing method of the present invention may optionally include steps other than the dispersion preparation step, the pre-composite sheet formation step, and the heat reduction step (hereinafter sometimes referred to as "other steps"). Other processes include, for example, a cooling process to cool the composite sheet obtained in the heating and reduction process.

[0042] <Dispersion liquid preparation process> In the dispersion preparation step, a dispersion containing carbon nanotubes, graphene oxide, and a solvent is prepared.

[0043] Examples of carbon nanotubes (CNTs) and graphene oxide (GO) used in the dispersion preparation process include those described above in relation to the composite sheet of the present invention.

[0044] In the dispersion, the mass ratio of GO to CNT (GO / CNT) is preferably 0.02 or higher, more preferably 0.04 or higher, preferably 0.50 or lower, more preferably 0.25 or lower, even more preferably 0.15 or lower, and even more preferably 0.10 or lower. If the mass ratio of GO to CNTs is within the above range, the conductivity and strength of the resulting composite sheet can be effectively improved. Furthermore, if the mass ratio of GO to CNTs is within the above range, the composite sheet of the present invention described above can be easily obtained.

[0045] The solvent used in the dispersion preparation step is not particularly limited, but examples include water; methanol, ethanol, and other alcohols. These may be used individually or in combination of two or more.

[0046] The method for preparing the dispersion is not particularly limited, but for example, a dispersion containing CNTs, GO, and a solvent can be prepared by mixing dispersion A containing CNTs and a solvent with dispersion B containing GO and a solvent. For mixing, for example, an ultrasonic disperser can be used. The solvents included in dispersion A and dispersion B are those listed above. The solvents included in dispersion A and dispersion B may be the same or different.

[0047] The solid content concentration of the dispersion prepared in the dispersion preparation step is, for example, 0.05% by mass or more and 5% by mass or less.

[0048] <Pre-composite sheet formation process> In the pre-composite sheet formation process, the solvent is removed while the dispersion prepared in the dispersion preparation process is placed on the substrate, thereby forming a pre-composite sheet.

[0049] The substrate used in the dispersion preparation process is not particularly limited, and for example, polyethylene terephthalate (PTFE) film, polyimide film, or a sheet made of cellulose fibers can be used. Furthermore, porous materials of the above-mentioned examples can also be used as the substrate. That is, porous substrates such as filters can also be used as the substrate.

[0050] Methods for removing the solvent while the dispersion is placed on a substrate include, for example, (1) placing the dispersion on a filter as a porous substrate and removing the solvent as a filtrate by suction filtration, and (2) coating the substrate with the dispersion to form a coating film and removing the solvent from the coating film by volatilization. Among these, method (1) is preferred because it yields a pre-composite sheet in which CNTs and GO are uniformly dispersed. In the case of method (1), the pre-composite sheet can usually be obtained as a filtration residue.

[0051] <Heat reduction process> In the heating and reduction step, the pre-composite sheet formed in the pre-composite sheet formation step is heated to reduce the graphene oxide in the pre-composite sheet. This makes it possible to obtain a composite sheet containing carbon nanotubes and reduced graphene oxide. In addition, during the heating and reduction process, the heating and reduction may be performed while pressing the pre-composite sheet perpendicular to its surface.

[0052] In the heating reduction step, the pre-composite sheet may or may not be removed from the substrate. That is, in the heating reduction step, only the pre-composite sheet may be heated and reduced, or the substrate may be heated and reduced together with the pre-composite sheet. Furthermore, if the substrate is heated and reduced together with the pre-composite sheet, the composite sheet may be removed from the substrate after heating and reduction or after any cooling step.

[0053] The atmosphere used to reduce GO in the pre-composite sheet is not particularly limited as long as it is an atmosphere capable of reducing GO, but examples include a vacuum atmosphere; an inert gas atmosphere such as nitrogen gas or a noble gas; and a reducing gas atmosphere. Among these, a vacuum atmosphere or an inert gas atmosphere is preferred when heating the pre-composite sheet because it allows for efficient reduction of GO.

[0054] The heating temperature when reducing GO in the pre-composite sheet is preferably 200°C or higher, more preferably 250°C or higher, and even more preferably 300°C or higher. If the heating temperature is above the lower limit mentioned above, GO can be efficiently reduced. The heating temperature used to reduce GO in the pre-composite sheet is, for example, 1000°C or less, but may also be 500°C or less.

[0055] The heating time for reducing GO in the pre-composite sheet is, for example, between 0.5 hours and 3 hours.

[0056] In the heating and reduction process, when heating and reducing while pressing the pre-composite sheet perpendicular to its surface, the pressing pressure is preferably 10 kPa or more, more preferably 100 kPa or more, more preferably 5000 kPa or less, and more preferably 1000 kPa or less. If the press pressure is above the lower limit mentioned above, the reduction in density of the composite sheet due to degassing during reduction can be effectively suppressed. On the other hand, if the press pressure is below the above upper limit, damage to the pre-composite sheet due to heating can be suppressed, and as a result, a good composite sheet can be produced.

[0057] In this embodiment of the present invention, the reduction in the heating reduction step is preferably carried out at a temperature of 200°C or higher and under a vacuum atmosphere or an inert gas atmosphere, since this allows for more efficient reduction of GO. [Examples]

[0058] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" used to express quantities refer to mass unless otherwise specified. In the examples, various measurements and evaluations were performed according to the following methods.

[0059] <Area A and Area B> Using a scanning electron microscope (SEM) (ZEISS, Gemini560) and an InLens detector, surface SEM images of the composite sheets obtained in the following examples and comparative examples were acquired under the conditions of 200x magnification, 3kV acceleration voltage, and WD4mm. In the obtained surface SEM images, the areas with high contrast (corresponding to areas where CNTs are exposed) and areas with low contrast (corresponding to areas where rGO is exposed) were binarized using image processing software (ImageJ / Fiji). During this process, noise reduction was performed using a median filter, and a threshold was set using a binarization algorithm (Intermodes). Next, the area of ​​the white region and the area of ​​the black region were calculated using the binarized image. The above procedure was performed on five surface SEM images, and the average area of ​​the white region and the average area of ​​the black region were calculated. The average area of ​​the white region was defined as the area A of the region where CNTs were exposed, and the average area of ​​the black region was defined as the area B of the region where rGOs were exposed.

[0060] <Film thickness and film density> The composite sheets obtained in the examples and comparative examples were cut using a cutter to a size of 1 cm x 1 cm to prepare the measurement samples. Next, the mass of the sample was measured using a precision balance (GR-200, Kensei Kogyo Co., Ltd.). Next, the film thickness of the sample was measured using a constant-pressure thickness gauge (Mitutoyo), and the measured value was taken as the film thickness of the composite sheet. Next, the volume of the sample was calculated from its size and film thickness. Then, the film density (mg / mm³) of the sample was calculated from its volume and mass. 3 ) was calculated.

[0061] <Conductivity> The composite sheets obtained in the examples and comparative examples were cut into 1 cm x 1 cm squares using a cutter to prepare measurement samples. Using a resistivity meter (Loresta-GP MCP-T610, manufactured by Mitsubishi Chemical Analytec Co., Ltd.), the conductivity (S / cm) was measured by pressing the resistivity meter's PSP probe (pin width 1.5 mm) against the center of the prepared measurement sample. The size of the measurement sample, film thickness, and probe type were entered into Loresta, and the resistance value was calculated using the correction coefficient in Loresta. The conductivity of the composite sheet was then calculated by converting the obtained resistance value.

[0062] <Tensile Test> The composite sheets obtained in the examples and comparative examples were cut into dumbbell-shaped No. 7 sheets as specified in JIS K 6251 using a punching machine to prepare measurement samples. Tensile tests were performed on the measurement samples using a tensile strength testing machine (Strograph VG, manufactured by Toyo Seiki Co., Ltd.) to measure the breaking strength of the composite sheets.

[0063] <Conductive> The conductivity of the composite sheet was evaluated using the measured conductivity according to the following criteria. A: Conductivity of 80.0 S / cm or higher B: Conductivity of 70.0 S / cm or higher C: Conductivity of 65.0 S / cm or higher D: Conductivity less than 65.0 S / cm

[0064] <Strength> The strength of the composite sheet was evaluated using the fracture strength obtained from the tensile tests, according to the following criteria. A: Breaking strength of 20.0 MPa or higher B: Breaking strength of 10.0 MPa or higher C: Breaking strength is less than 10.0 MPa D: Tensile test measurement not possible

[0065] (Example 1) <Dispersion liquid preparation process> A CNT-containing ethanol dispersion with a concentration of approximately 0.3% was prepared by adding 1 kg of ethanol to 3 g of SGCNT (manufactured by Zeon Corporation, ZEONANO® SG101) and passing the mixture through a jet mill (manufactured by Biryu Co., Ltd., BERYU SYSTEM PRO) for 3 to 5 passes. Next, to 9.5 g of the obtained CNT-containing ethanol dispersion, 0.15 g of graphene oxide (GO) aqueous dispersion (manufactured by Nishina Material Co., Ltd.) with a concentration of 1% graphene oxide (GO), and 10 g of ultrapure water were added. After stirring several times with a stirring rod, the mixture was dispersed for 10 minutes at an output of 70 W using an ultrasonic disperser (CPX1800H-J, manufactured by Bransonic) to obtain a dispersion containing CNTs, GO, and a solvent.

[0066] <Pre-composite sheet formation process> A PTFE membrane filter was set in a suction filter, and after placing the dispersion liquid on the filter, the solvent was removed by suction with a pump to form a pre-composite sheet containing CNTs and GO on the filter.

[0067] <Heat reduction process> The pre-composite sheet was peeled off the filter and recovered. The recovered pre-composite sheet was placed in an inert oven (manufactured by KOYO THERMO SYSTEMS), and the oven was gas-purged with N2 gas at a flow rate of 10 L / min for 15 minutes. Then, the oven was heated at a heating rate of 11°C / min. When the temperature inside the oven reached 350°C, this temperature was maintained for 30 minutes, and then cooled to room temperature to obtain a composite sheet containing CNTs and rGO. Various measurements and evaluations were performed using the obtained composite sheet. The results are shown in Table 1.

[0068] (Example 2) Except for changing the amount of CNT-containing ethanol dispersion used from 9.5 g to 8 g and the amount of GO aqueous dispersion used from 0.15 g to 0.6 g in the dispersion preparation process, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0069] (Example 3) Except for changing the amount of CNT-containing ethanol dispersion used from 9.5 g to 5 g and the amount of GO aqueous dispersion used from 0.15 g to 1.5 g in the dispersion preparation process, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0070] (Comparative Example 1) Except for not using GO aqueous dispersion in the dispersion preparation process, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0071] (Comparative Example 2) Except for not using a CNT-containing ethanol dispersion in the dispersion preparation process, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0072] [Table 1]

[0073] As is clear from Table 1, the composite sheet in the example achieves both high conductivity and high strength. [Industrial applicability]

[0074] According to the present invention, a composite sheet that achieves both high conductivity and high strength can be provided. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a composite sheet that achieves both high conductivity and high strength.

Claims

1. A composite sheet comprising carbon nanotubes and reduced graphene oxide, A composite sheet in which, on at least one surface of the composite sheet, the ratio of the area B of the area where the reduced graphene oxide is exposed to the area A of the area where the carbon nanotubes are exposed is 0.1 or more and 50.0 or less.

2. The membrane density is 0.10 g / cm³. 3 1.40g / cm or more 3 The composite sheet according to claim 1, which is as follows:

3. The composite sheet according to claim 1 or 2, wherein the film thickness is 5 μm or more and 100 μm or less.

4. The composite sheet according to claim 1 or 2, wherein the mass ratio of reduced graphene oxide to carbon nanotubes is 0.02 or more and 0.50 or less.

5. A composite sheet comprising carbon nanotubes and reduced graphene oxide, A composite sheet obtained by heating and reducing a pre-composite sheet formed by removing the solvent from a dispersion containing the carbon nanotubes, graphene oxide, and the solvent.

6. A method for producing a composite sheet containing carbon nanotubes and reduced graphene oxide, A dispersion preparation step involves preparing a dispersion containing the carbon nanotubes, graphene oxide, and a solvent. A pre-composite sheet forming step, in which the solvent is removed while the dispersion is placed on the substrate, and a pre-composite sheet is formed. A heating and reduction step is performed by heating the pre-composite sheet to reduce the graphene oxide in the pre-composite sheet. A method for manufacturing a composite sheet, including the following:

7. The method for manufacturing a composite sheet according to claim 6, wherein the reduction is performed at a temperature of 200°C or higher and under a vacuum atmosphere or an inert gas atmosphere.

Citation Information

Patent Citations

  • Rgo / CNT mixed film and production method of rgo / CNT mixed film

    JP2022080406A